Frugivoria por morcegos (Chiroptera: Phyllostomidae) na Mata atlântica do Nordeste e padrões germinativos de sementes após passagem pelo sistema digestivo - Pereira, Arivania Santos (2017)
Chiropterocory has been identified as the most effective means of dispersal in the tropics, 549 species of neotropical plants have already been compiled in analyzes of dispersion by bats. Understanding the processes that interfere in the choice of the item to be dispersed, as well as the mechanisms that act on seed dispersal effectiveness, are essential steps in the understanding of the bat-plant interactions. This study aimed to evaluate the food ecology of a group of Carollia perspicillata, also evaluating the endozoochory effect of this species and of Platyrrhinus lineatus on the germination patterns of the main plant species consumed by them. The study was carried out in two areas of Atlantic Forest. The first one is a limestone under-rock shelter, inhabited by bats of the species Carollia perspicillata in the municipality of Laranjeiras-Sergipe. The second area was the campus of the Federal University of Sergipe, which includes a group of Platyrrhinus lineatus, residentsfor at least five years. The fecal sampling for the analysis of endozoochory by P. lineatus and C. perspicillata, and the analysis of the diet for the latter, were carried out by means of plastictarpaulins extended below the groupings of the respective species, during 72 hours/month in the period of one year. In parallel, phenological observations were made. The germination tests were performed at ambient conditions and formed by two treatments, one control group and one test group. Each treatment consisted of four replicates by species with 400 seed each. Mean germination time (MGT), germination speed index (GSI), seed synchrony and germinability were considered. In terms of food ecology, approximately 323,400 seeds were obtained, classified into 16 species and 12 families. Thesynzoochorous species represented the smallest portion of the general seed sample (n = 5), which was predominated by endozoochorous seeds (n = 11). Five of these species (Annona montana, Syagrus coronata, Senna georgica, Aegiphila vitelliniflora and Chomelia obtusa) are being reported for the first time in the group diet. The species with the highest numbers of seeds found in the shelters were Piper amalago (n = 160,594), Solanum paniculatum (79,322) and Maclura tinctoria (60,691). Although the number of seeds of P. amalago was considerably higher, there were no significant differences between the consumption of these three main species in generalnor in the different periods of the year. The richness of plant species in the diet did not differ significantly between the periods of the year. C. perpicillata kept the germination patterns of the M. tinctoria species neutral. In P. amalago, endozoochory was also neutral for germinability, but the MGT, GSI and Synchrony of the seeds of the test group were significantly lower than those in the control group. With the exception of the germinability of the test group that was greater than the control, the germinative parameters of S. paniculatum remained neutral. For P. lineatus, except for the MGT test, which was significantly lower than the control group, no significant differences were observed for S. paniculatum. C. perspicillata has been shown to significantly increase the germinability of S. paniculatum in relation to P. lineatus. The data of this study shows the functional role of these species of bats in the dispersal effectiveness. It is suggested the execution of endozoochory studies with concise experimental designs that contemplate the amplitude of variables that can interfere in the process.